2002
DOI: 10.1002/ijc.10223
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome anomalies in pancreatic endocrine tumors

Abstract: We have investigated the status of sex chromosomes in 40 pancreatic endocrine tumors (PETs) using 2 complementary techniques: microsatellite and interphase FISH analysis. Twenty-five tumors were from female and 15 from male patients and included 31 nonfunctioning and 9 functioning PET (6 insulinomas, 2 glucagonomas and 1 VIPoma). Microsatellite and FISH analysis showed concordant results in all cases. PETs from females showed frequent loss of chromosome X (40%) whereas PETs from males showed relatively frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 34 publications
3
33
0
1
Order By: Relevance
“…Future studies will determine if these genes are involved in insulinoma oncogenesis. Deletions of other chromosomal regions that were reported to be associated with malignant behavior of EPTs, such as 1p, 3p, 3q, 11q, 17p, 22q and X (Chung et al 1997, Beghelli et al 1998, Ebrahimi et al 1999, Hessman et al 1999, Barghorn et al 2001a, b, Guo et al 2002, Missiaglia et al 2002, Wild et al 2002, were only occasionally observed in this CGH study on insulinomas. Losses of chromosome 3p and 3q were identified significantly more frequently in the malignant insulinomas, but only at low frequencies of 17 and 33% respectively.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Future studies will determine if these genes are involved in insulinoma oncogenesis. Deletions of other chromosomal regions that were reported to be associated with malignant behavior of EPTs, such as 1p, 3p, 3q, 11q, 17p, 22q and X (Chung et al 1997, Beghelli et al 1998, Ebrahimi et al 1999, Hessman et al 1999, Barghorn et al 2001a, b, Guo et al 2002, Missiaglia et al 2002, Wild et al 2002, were only occasionally observed in this CGH study on insulinomas. Losses of chromosome 3p and 3q were identified significantly more frequently in the malignant insulinomas, but only at low frequencies of 17 and 33% respectively.…”
Section: Discussionmentioning
confidence: 52%
“…The few malignant insulinomas that have been genetically analyzed by molecular allelotyping and CGH were mainly part of larger studies on EPTs, including different functioning and non-functioning subtypes (Chung et al 1998, Speel et al 1999, Stumpf et al 2000. Several markers for malignant or metastatic progression in EPTs have been indicated, in particular loss of chromosomes 1 (Ebrahimi et al 1999), 3p (Chung et al 1997, Hessman et al 1999, Barghorn et al 2001a, 3q (Chung et al 1998, Guo et al 2002), 6q22-24 (Barghorn et al 2001b, 11q13 (Hessman et al 1999), 17p (Beghelli et al 1998), 22q (Chung et al 1998, Wild et al 2002 and X (Missiaglia et al 2002). These do, however, require further validation in larger series of individual EPT subtypes, including insulinomas.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, loss of chromosome X was described in 40% of cases of PETs from females, while loss of chromosome Y was present in 36% of cases of PETs from males. In the same study, sex chromosome alterations were associated with the presence of metastases, higher proliferation index and worse prognosis (Missiaglia et al 2002).…”
Section: Loss Of Heterozygositymentioning
confidence: 69%
“…Indeed, the association between X chromosome allelic losses and malignancy has been clearly documented in endocrine tumors of the stomach 7 and pancreas. 6,28 Moreover, X chromosome LOH has recently been found to correlate with aggressive post operative tumor X chromosome in lung endocrine tumors T D'Adda et al growth in pancreatic gastrinomas. 29 In contrast, endocrine tumors of midgut and hindgut origin, even if malignant, did not present a significant occurrence of X chromosome losses.…”
Section: Discussionmentioning
confidence: 99%